The Effect of Tera Gymnastics on Blood Pressure Hypertensive Patients in The Cibodasari Health Center Tangerang City - Sari, Galuh Puspita; Wasludin, Wasludin (Politeknik Kesehatan Kementerian Kesehatan Banten, 2024)
Introduction: Hypertension is generally defined as the condition where systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg. Efforts to treat and manage hypertension early include two, namely with non-pharmacological and pharmacological therapies, for noon pharmacological therapies such as lifestyle changes can lower blood pressure. Increased physical activity routinely carried out will reduce blood pressure, this can occur because physical activity, such as gymnastics can make the heart strong and the flow of blood that will be pumped throughout the body can also run well without the need for hard effort from the heart, one type of exercise that can reduce blood pressure is tera gymnastics. Purpose: This study aims to determine the effect of tera gymnastics on blood pressure in hypertensive patients in the Cibodasari Health Center Working Area, Cibodas District, Tangerang City. Method: The research design used was quasi-experimental with a one-group pretest-posttest design. The number of samples taken was 14 respondents conducted on March 22 to 25, 2023. Probability sampling technique using simple random sampling. Results: This study used the T-dependent test, with an average decrease in systolic blood pressure by 8 mmHg and diastolic by 6 mmHg, from both data obtained a significance value (p-value = 0,000 for systolic blood pressure, and p-value = 0,001 for diastolic blood pressure) which means the p-value < 0,05. Concluded: In this study, there is an effect of hypertensive patients in the Cibodasari Health Center Working Area, Cibodas District, Tangerang City.